2013
DOI: 10.1093/jxb/ert292
|View full text |Cite
|
Sign up to set email alerts
|

Grain development in Brachypodium and other grasses: possible interactions between cell expansion, starch deposition, and cell-wall synthesis

Abstract: To explain the low levels of starch, high levels of (1,3;1,4)-β-glucan, and thick cell walls in grains of Brachypodium distachyon L. relative to those in other Pooideae, aspects of grain development were compared between B. distachyon and barley (Hordeum vulgare L.). Cell proliferation, cell expansion, and endoreduplication were reduced in B. distachyon relative to barley and, consistent with these changes, transcriptional downregulation of the cell-cycle genes CDKB1 and cyclin A3 was observed. Similarly, redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 58 publications
4
83
1
Order By: Relevance
“…It is the most highly expressed CSLF gene in most tissues of barley (Hordeum vulgare), wheat (Triticum aestivum), Brachypodium distachyon, and rice (Oryza sativa), including developing seedling leaf, coleoptiles, and endosperm (Burton et al, 2008;Kimpara et al, 2008;Doblin et al, 2009;Nemeth et al, 2010;Pellny et al, 2012;Vega-Sánchez et al, 2012;Suliman et al, 2013;Trafford et al, 2013;Schreiber et al, 2014). When CSLF6 expression is reduced either by knockdown or knockout via mutation or T-DNA insertion (Tonooka et al, 2009;Nemeth et al, 2010;Taketa et al, 2012;Vega-Sánchez et al, 2012;Hu et al, 2014), a significant reduction in MLG is observed in both vegetative and floral tissues, indicating its gene product is responsible for the synthesis of the majority of MLG in grasses.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most highly expressed CSLF gene in most tissues of barley (Hordeum vulgare), wheat (Triticum aestivum), Brachypodium distachyon, and rice (Oryza sativa), including developing seedling leaf, coleoptiles, and endosperm (Burton et al, 2008;Kimpara et al, 2008;Doblin et al, 2009;Nemeth et al, 2010;Pellny et al, 2012;Vega-Sánchez et al, 2012;Suliman et al, 2013;Trafford et al, 2013;Schreiber et al, 2014). When CSLF6 expression is reduced either by knockdown or knockout via mutation or T-DNA insertion (Tonooka et al, 2009;Nemeth et al, 2010;Taketa et al, 2012;Vega-Sánchez et al, 2012;Hu et al, 2014), a significant reduction in MLG is observed in both vegetative and floral tissues, indicating its gene product is responsible for the synthesis of the majority of MLG in grasses.…”
Section: Introductionmentioning
confidence: 99%
“…These factors, together with the speed with which the reserves are released to support seedling growth after germination, are also important determinants of seedling vigor and hence crop establishment. The total number of cells in the endosperm is believed to influence grain size (Trafford et al, 2013).…”
mentioning
confidence: 99%
“…From cellularization (8 DAF) to maximum fresh weight, which can be reached 19 DAF, the number of cells across the endosperm lobe varies little and the endosperm area only increased 2.5-fold on the mid-grain cross-section of Brachypodium. In comparison, over the same developmental period in barley, the cell number increased 2-fold and the area increased 15-fold (Trafford et al 2013). Much reduced expression of cell-cycle-related genes cyclin A3 and Fig.…”
Section: Cell Differentiation and Maternal Tissue Organizationmentioning
confidence: 93%
“…Bar ¼ 100 μm (Top), 20 μm (Bottom). Reproduced with permission from Guillon et al (2012) and Journal of Experimental Botany CDKB1 indicated that the low rate of cell proliferation in Brachypodium endosperm is probably due to the blocking of mitosis (Trafford et al 2013).…”
Section: Cell Differentiation and Maternal Tissue Organizationmentioning
confidence: 99%
See 1 more Smart Citation